2011
DOI: 10.1016/j.febslet.2011.03.060
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β-induced erythrocytic damage and its attenuation by carotenoids

Abstract: Edited by Jesus AvilaKeywords: Erythrocyte Amyloid b-peptide Oxidative injury Phospholipid hydroperoxide Alzheimer's disease a b s t r a c tThe presence of amyloid b-peptide (Ab) in human blood has recently been established, and it has been hypothesized that Ab readily contacts red blood cells (RBC) and oxidatively impairs RBC functions. In this study, we conducted in vitro and in vivo studies, which provide evidence that Ab induces oxidative injury to RBC by binding to them, causing RBC phospholipid peroxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 29 publications
3
57
0
Order By: Relevance
“…Exposure of RBCs exposed to Aβ on the luminal surface of cerebral microvessels induces the erythrocytes' adhesion to endothelial cells and affects endothelial functionality [68] [69]. In agreement with these notions, Down syndrome patients with elevated Aβ levels in blood plasma were reported to have a greater risk of developing AD [70,71].Oxidative stress & altered energy production in RBCs Aβ binding induces oxidative injury to RBCs and causes the accumulation of phospholipid hydroperoxides, a specific marker for RBC membrane oxidative injury [72]. Moreover, an inverse relationship was seen between RBC concentrations of phospholipid hydroperoxides and carotenoids in AD patients [72].…”
supporting
confidence: 59%
See 2 more Smart Citations
“…Exposure of RBCs exposed to Aβ on the luminal surface of cerebral microvessels induces the erythrocytes' adhesion to endothelial cells and affects endothelial functionality [68] [69]. In agreement with these notions, Down syndrome patients with elevated Aβ levels in blood plasma were reported to have a greater risk of developing AD [70,71].Oxidative stress & altered energy production in RBCs Aβ binding induces oxidative injury to RBCs and causes the accumulation of phospholipid hydroperoxides, a specific marker for RBC membrane oxidative injury [72]. Moreover, an inverse relationship was seen between RBC concentrations of phospholipid hydroperoxides and carotenoids in AD patients [72].…”
supporting
confidence: 59%
“…Moreover, an inverse relationship was seen between RBC concentrations of phospholipid hydroperoxides and carotenoids in AD patients [72]. Erythrocytes do not have sufficient mechanisms to repair oxidized lipids in their membranes, which leads to the accumulation of these products in the membranes as well as inside the cell during the erythrocyte's lifespan.…”
Section: Aβ-induced Morphological Changes In Erythrocytesmentioning
confidence: 97%
See 1 more Smart Citation
“…L supplementation has been shown to improve verbal fluency in older women , and plasma carotenoid levels have been associated with performance across a range of cognitive domains (Akbaraly et al, 2007) as well as being lower in individuals with mild cognitive impairment and Alzheimer's disease (AD) compared with normal controls (Rinaldi et al, 2003). Xanthophylls can attenuate the inflammatory effect of Aβ on the vasculature, thus potentially reducing the risk of AD (Nakagawa et al, 2011). Furthermore, the concentration of Z in blood serum is inversely associated with the severity of white matter lesions in the brains of nondemented older adults (den Heijer et al, 2001).…”
mentioning
confidence: 99%
“…In our murine study 10 , oral administration of a lutein concentrate showed its incorporation into erythrocytes and distribution in the phospholipid bilayers. This treatment resulted in decreased erythrocyte PLOOH levels.…”
Section: Introductionmentioning
confidence: 99%